High intensity intermittent vs race pace 200-m swimming - Beidaris, N.; Platanou, T. (Scientific Journal of Sport and Performance, 2025)
This study aimed to investigate the physiological responses and performance characteristics of high intensity intermittent swimming with different resting intervals, compared to high intensity race pace continuous swimming. Twelve young male competitive swimmers (aged: 15.46 ± 1.45 years) were tested in 4 exercise conditions: in a continuous maximum 200-m freestyle swim and in 4x50-m freestyle with 5, 10 and 20s rest intervals between splits. In all conditions, oxygen consumption, blood lactate concentration, heart rate, performance characteristics, and ratings of perceived exertion were measured.Blood lactate concentration and oxygen uptake were no different between conditions (p = .98 and p = .39). Overall performance time of the 200-m swimming was faster with the 20s rest intervals (137.12 ± 7.78 vs 149.33 ± 9.27 sec, p = .004), and a heart rate was higher (195.38 ± 11.87 vs 184.23 ± 5.26 beat·min-1, p = .01) than in 200-m continuous swimming. The velocity and the number of strokes remained constant between every 50-m split of the 4x50-m swim with 20s rest interval, as opposed to the decreasing velocity in the continuous high intensity race pace 200-m condition (p < .05). Differences in the intermittent conditions of shorter rest interval (5 and 10-sec) were limited only to decrements of speed between the splits (p < .05). Despite the similar lactate and VO2 responses between all conditions, swimmers were swimming at a higher intensity and a constant velocity in the 4x50-m trial with 20s rest interval, while the conditions with 5 and 10-sec rest intervals matched the performance characteristics of the 200-m continuous swim.